A novel hybrid genetic algorithm to reduce the peak-to-average power ratio of OFDM signals. (December 2019) - Sharifi, Abbas Ali; Hosseinzadeh Aghdam, Mehdi
Abstract: Orthogonal frequency division multiplexing (OFDM) is an effective approach for high rate data transmission in telecommunication systems. The high peak-to-average power ratio (PAPR) is one of the main drawbacks of the OFDM systems. Partial transmit sequence (PTS) is an efficient method to decrease the PAPR of OFDM signals. But, the PTS technique needs an exhaustive search over all combinations of phase rotation factors and the computational complexity grows exponentially with the number of sub-blocks. To reduce the search complexity, we introduce a novel hybrid genetic algorithm (HGA) in the PTS technique. The important aspect of the proposed method is the choice of salient phase factors to reduce the high PAPR. The proposed HGA-PTS approach incorporates novel local search operations that are designed and embedded in the genetic algorithm to explore the optimum phase factors. Numerical simulations are performed for 16-QAM modulated symbols and the obtained results show that the HGA-PTS significantly reduces both the PAPR and search complexity.